2010
DOI: 10.1038/leu.2010.65
|View full text |Cite
|
Sign up to set email alerts
|

High-density single nucleotide polymorphism array analysis and ASXL1 gene mutation screening in chronic myeloid leukemia during disease progression

Abstract: We have undertaken a genome-wide single nucleotide polymorphism (SNP) array analysis of 41 chronic myeloid leukemia (CML) patients. In total, 44 regions of uniparental disomy (UPD) 43 Mb were identified in 24 of 32 patients in chronic phase (CP), and 21 regions of UPD 43 Mb were identified in 13 of 21 patients in blast crisis (BC). Chromosome 8 had the highest frequency of UPD regions in both CP and BC samples. Eight recurrent regions of UPD were observed among the 41 patients, with chromosome 8 showing the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 40 publications
2
71
1
Order By: Relevance
“…These two mutations have been reported at similar rates in previous studies of AML and CMML. 10,11,[17][18][19][20][21] The remaining six mutations were found once each. Three of them were previously unreported: G652S, L817fs*1, and L866X.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…These two mutations have been reported at similar rates in previous studies of AML and CMML. 10,11,[17][18][19][20][21] The remaining six mutations were found once each. Three of them were previously unreported: G652S, L817fs*1, and L866X.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, copious clinical studies showed that ASXL1 is altered in multiple forms of myeloid malignancies, including myelodysplastic syndrome (MDS), myeloproliferative neoplasms (MPN), MDS/MPN (such as chronic myelomonocytic leukemia [CMML] and juvenile myelomonocytic leukemia [JMML]), and acute myeloid leukemia (AML). [6][7][8][9][10][11][12] Alterations in ASXL1 are generally associated with signs of aggressiveness and poor prognosis in patients with CMML, MDS, myelofibrosis, and AML. [13][14][15][16][17] ASXL1 alterations in myeloid malignancies have been reported as mutations and/or deletion, with the majority being frameshift and nonsense mutations, [6][7][8][9][10][11][12] resulting in C-terminal truncation of the protein upstream of the PHD finger.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Alterations in ASXL1 are generally associated with signs of aggressiveness and poor prognosis in patients with CMML, MDS, myelofibrosis, and AML. [13][14][15][16][17] ASXL1 alterations in myeloid malignancies have been reported as mutations and/or deletion, with the majority being frameshift and nonsense mutations, [6][7][8][9][10][11][12] resulting in C-terminal truncation of the protein upstream of the PHD finger. A recent study showed that truncated forms of the ASXL1 protein were undetectable in leukemia samples with ASXL1 mutations, suggesting that these mutations are likely "bona fide loss-of-function" disease alleles.…”
Section: Introductionmentioning
confidence: 99%
“…All other sequence variations have already been described as SNPs (data not shown). Recently, Boultwood et al 8 have reported ASXL1 mutations in 6 of 41 (14.6%) patients from both CP and blast crisis CML. In our study, ASXL1 alterations (8.8%) were not detected when patients reached molecular response, and were not necessarily found at relapse.…”
mentioning
confidence: 99%